ANALYSIS OF FACTORS INFLUENCING CONSUMPTION RATES BY VOTING COMMITTEES - Fadillah, Muhammaf Ivan (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
Every household will not be separated from consumption behavior, both to meet primary needs and secondary needs in the survival of the household. The purpose of this study was to find out what factors and how influential they have on the consumption level of the Voting Committee (PPS) of 13 villages in Kotaanyar Kabupaten Probolinggo District. This study uses a quantitative approach with primary data. This study used multiple regression tests. The results of this study show that the salary variable and the side income variable have a positive and significant effect while the variable number of family dependents has no significant effect on consumption.